SIMULATION FOR THE PRESSURE LOSS OF AUTOMOTIVE EXHAUST MUFFLER - WANG ZhiJie; LI JianXing; XU XiaoJun (Jixie qiangdu)
With the method of CFD,pressure loss of the muffle in different flow rates were calculated by using numerical calculation. Then based on the FLUENT software,the pressure loss of the muffle was simulated,and the influence of structure on the pressure loss was analyzed. On the basis,the structure of the muffler was optimized. The results show that the reasonable arrangement of the intubation and perforated pipe can reduce the pressure loss effectively,which provided a theoretical basis for the optimization design of the muffler.